Preparation and Studies of ZnFe2O4–CeO2 Nanopowder via Self Combustion Glycine Nitrate Process for Methanol Steam Reforming Hydrogen Production - Shu-Han Juang; Chung‐Lun Yu; Subramanian Sakthinathan; Tetsu Yonezawa; Ching‐Lung Chen; Te‐Wei Chiu; Naratip Vittayakorn (ACS Sustainable Resource Management, 2025)
As fossil fuels have finite resources and environmental drawbacks, there’s a growing interest in cleaner, renewable energy. Hydrogen (H2) is seen as a promising alternative to petroleum due to its non-toxic, clean combustion that only produces water and avoids carbon dioxide emissions. In this study, different ratios of ZnFe2O4–CeO2 nanopowder were synthesized via the glycine nitrate process (GNP). The ZnFe2O4–CeO2 nanopowder catalyst was prepared by GNP, which was immensely porous and had a cotton-like structure. Moreover, the glycine nitrate process, which is a synthesis technology, can offer the advantages of low cost, simplicity, and speed and create a porous structure for the catalyst. The BET measurement revealed that the specific surface area of the as-combusted ZnFe2O4–CeO2 nanopowder varied from 8.48 m2/g to 19.82 m2/g. Hydrogen production through the SRM process was monitored by using a gas chromatograph equipped with a thermal conductivity detector. The 20ZnFe2O4–80CeO2 powder had the highest H2 production without activation, reaching 7566.08 mL STP min–1 g-cat–1 at a reaction temperature of 550 °C achieved at an N2 flow rate of 30 sccm. This study indicates that the glycine nitrate process imparts a porous structure to the catalyst, thereby increasing hydrogen production. Moreover, suitable incorporation of CeO2 could improve the catalytic performance in the SRM process on hydrogen. Therefore, ZnFe2O4–CeO2 nanopowders may have significant economic prospects.
Keywords: Catalytic Processes in Materials Science; Catalysts for Methane Reforming; Catalysis and Hydrodesulfurization Studies